2020
DOI: 10.18502/ijph.v49i11.4729
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Symptoms in Patients Recovered from COVID-19

Abstract: Background: COVID-19 is a new disease, so we don’t know what comes next. Since information on delayed symptoms is limited, this study was conducted to assess the frequency of delayed symptoms in patients with COVID-19. Methods: This follow-up cross-sectional study was conducted in a referral general hospital in Tehran, Iran from Feb to Apr 2020. Two hundred patients hospitalized for COVID-19 and were discharged were assessed for delayed symptoms 6 wk after discharge. Results: The mean age of the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 24 publications
2
34
0
4
Order By: Relevance
“… 4 Moradian et al reported that 42% of their patients were symptom‐free, while fatigue persisted in 19.5%, followed by dyspnea (18.5%), weakness (18%), and activity intolerance (14.5%). 8 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 4 Moradian et al reported that 42% of their patients were symptom‐free, while fatigue persisted in 19.5%, followed by dyspnea (18.5%), weakness (18%), and activity intolerance (14.5%). 8 …”
Section: Discussionmentioning
confidence: 99%
“…In the study of Huang et al, which included 1733 discharged patients with COVID‐19, the most common symptoms were fatigue or muscle weakness (63%) and sleep difficulties (26%) 4 . Moradian et al reported that 42% of their patients were symptom‐free, while fatigue persisted in 19.5%, followed by dyspnea (18.5%), weakness (18%), and activity intolerance (14.5%) 8 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…84 However symptom duration, patient populations, and length of follow-up are highly variable between studies, with reported rates of full recovery between 13% and 86% at follow-up ranging from 30 to 186 days (Table 2). 7173,75,78,83,85103…”
Section: Covid-19 and Me/cfsmentioning
confidence: 99%
“…Ozçelik Korkmaz et al (2021) [d] Salahuddin et al (2020) [e] Salepci et al (2021) [f] Savtale et al (2021) [g] Carfi et al (2020) [h] Davis (2020) [i] Elibol (2021) [j] Membrilla et al (2020) [k] Rocha-Filho & Magalhaes (2020) [l] Stavem et al (2020) [m] Micarelli et al (2020) [n] Dror et al (2021) [o] Go€ ertz et al (2020) [p] Lechien et al (2020) [q] Daikhes et al (2020) [r] Freni et al (2020) [s] Iltaf et al (2020) [t] Karimi et al (2020) [u] Khalaf, M. (2020) [v] Klopfenstein et al (2020) [w] Mustafa (2020) [x] Moradian et al (2020) [y] Cirulli (2020) [z] Kamal et al (2021) [ Ð ] Munro et al (2020) [ §] Viola et al (2020). where there was uncertainty or missing data.…”
mentioning
confidence: 99%